The Influence of Middle Eastern Tourists on Local Community in Cisarua Bogor in the Perspective of Identity Politics and Communitarian Citizenship - Ngenget, Indiana; Indarwati, Netik (Political Science Program, Universitas Negeri Semarang, 2020)
This research aimed to analyze the influence of Middle Eastern tourists on local community in Cisarua Bogor in the perspective of Identity Politics and Communitarian Citizenship. This research usedqualitative with a descriptive explanatory research type. Data collection techniques used were observation, in-depth interviews, and library research. The results of this research showed that Middle Eastern tourists positively encouraged tourism activities and economic development of local community but there was an emergence of social, political, and cultural problems such as identity crisis. Local community in Cisarua as part of Indonesia is faced with the presence of a minority group namely Arab tourists who visit this region at certain times and demand a recognition of their identity. So that the localcommunity in Cisarua is faced with multicultural life because they touch and interact with values that are different from what they have. Empirically, from a political perspective, Middle Eastern tourists have encouraged the formation of identity politics and the issue of communitarian citizenship while local values are increasingly eroded. The problem of communitarian citizenship is reflected in the phenomenon of Arabic villages through the rise of Arabic writing in business, the dominance of Arabic culture, Arabic food, and so on. The thick Middle Eastern culture in tourist areas becomes a problem when dealing with local culture and nationalism as a challenge for a sovereign nation. The novelty of this research is the influence of Middle Eastern tourists in the perspective of Political Science on identity politics and communitarian citizenship.